Optimization of Scheduling for Hydro-thermal Power Generation and Transmission Including Pumped Storage Systems - Álvarez, Gonzalo (2017)
This work presents a novel approach for solving the short-term scheduling of hydro-thermal power generation, including pumped storage systems and transmission constraints. The problem addressed is known as Security Constrained Unit Commitment (SCUC). Pumped Storage Units (PSUs) are important in electric systems during the off-peak and the peak demand periods, providing economic and technical benefits. Linear aproximations are applied to nonlinear equations of this kind of mathematical problems which are: fuel cost functions, generation-discharge curves of PSUs and transmission constraints modeled with Alternating Current power flow model. Thus, MILP models are presented for the problem addessed. To prove the efficiency of the proposed models, two systems with PSUs will be tested: a modified 6-bus and the IEEE 31-bus power system. Results show that the proposed MILP models allow: modeling the SCUC problem more realistically, obtaining feasible solutions within efficient computational times, and reaching production cost savings up to almost 15% compared to power systems that lack capacities to pumping water. Several indicators obtained from results are presented through graphs, as a tool for improving operation and maintenance of power systems. The analysis of these indicators and the graphic interpretation allow to identify and classify critical parts of systems as well as to make recommendations about future system improvements.